Stability of Solutions of a Quasilinear Index-2 Tractable Differential Algebraic Equation by the Lyapunov Second Method - Vu Tuan; Pham Van Viet (Український математичний журнал, 2004)
The Lyapunov second method is an important tool in the qualitative theory of ordinary differential equations. In this paper, we consider the behavior of solutions of quasilinear index-2 tractable differential algebraic equations. Using the Lyapunov second method, we prove sufficient conditions for the stability of zero solution of such equations. Другий метод Ляпупова є важливим інструментом в якісній теорії звичайних диференціальних рівнянь. У даному етапі розглянуто поведінку розв'язків кназіліпійпих розв'язуваних за індексом 2 диференціальних алгебраїчних рівнянь. За допомогою другого методу Ляпунона доведено достатні умови стійкості нульового розв'язку таких рівнянь.